Delayed mirror visual feedback presented using a novel mirror therapy system enhances cortical activation in healthy adults - Hsin-Min Lee; Ping‐Chia Li; Shih-Chen Fan (2015)
Mirror visual feedback (MVF) generated in mirror therapy (MT) with a physical mirror promotes the recovery of hemiparetic limbs in patients with stroke, but is limited in that it cannot provide an asymmetric mode for bimanual coordination training. Here, we developed a novel MT system that can manipulate the MVF to resolve this issue. The aims of this pilot study were to examine the feasibility of delayed MVF on MT and to establish its effects on cortical activation in order to understand how it can be used for clinical applications in the future.Three conditions (no MVF, MVF, and 2-s delayed MVF) presented via our digital MT system were evaluated for their time-course effects on cortical activity by event-related desynchronization (ERD) of mu rhythm electroencephalography (EEG) during button presses in 18 healthy adults. Phasic ERD areas, defined as the areas of the relative ERD curve that were below the reference level and within -2-0 s (P0), 0-2 s (P1), and 2-4 s (P2) of the button press, were used.The overall (P0 to P2) and phasic ERD areas were higher when MVF was provided compared to when MVF was not provided for all EEG channels (C3, Cz, and C4). Phasic ERD areas in the P2 phase only increased during the delayed-MVF condition. Significant enhancement of cortical activation in the mirror neuron system and an increase in attention to the unseen limb may play major roles in the response to MVF during MT. In comparison to the no MVF condition, the higher phasic ERD areas that were observed during the P1 phase in the delayed-MVF condition indicate that the image of the still hand may have enhanced the cortical activation that occurred in response to the button press.This study is the first to achieve delayed MVF for upper-limb MT. Our approach confirms previous findings regarding the effects of MVF on cortical activation and contributes additional evidence supporting the use of this method in the future for upper-limb motor training in patients with stroke.